LKS Berbasis RME Menggunakan Cabri 3D untuk Koneksi Matematis Siswa pada Bangun Ruang Bidang Lengkung - Sukmaningthias, Novika; Sari, Novita; Somakim, Somakim; Susanti, Ely; Safitri, Desi (Edumatica : Jurnal Pendidikan Matematika, 2022)
This research is development research that aims to create student worksheets based on RME with Cabri 3D to train junior high school students' mathematical connections on solid with non-flat surface materials that are valid, practical, and have potential. The development model used is ADDIE. This research was conducted at SMP Negeri 10 Palembang in the even semester of the 2020/2021 academic year. The subjects in this study were students of IX Class. This study consisted of two stages, Preliminary and formative evaluation. Walkthrough and interview data contained comments and suggestions from validators and students. Questionnaire data to see the practicality of the developed Student worksheet. All data were analyzed using descriptive qualitative methods. in the analysis, it was found that the student worksheet was built with valid criteria based on the validator results and practical. The questionnaire sheets with an average of 85.67%, which is very practical according to the criteria. The test showed the students' mathematical connection ability was categorized as good with an average of 87.88% after using the developed student worksheet. Based on the results obtained, the developed student worksheet meets the valid, practical and effective criteria.